The Sports Business in The Pacific Rim : Economics and Policy - Lee, Young Hoon; Fort, Rodney (Sports Economics, Management and Policy,, 2015)
Following consistent and rapid general economic growth, Pacific Rim countries have grown as a major force in sports. Australia, China, Japan and Korea populated the top ten medals list at the 2012 London Olympics. Pacific Rim countries are major consumers of international sports and domestic professional sports have expanded continuously over time. Nippon Professional Baseball and the Korean Baseball Organization are the second and third largest baseball leagues measured by attendance and revenue following Major League Baseball in the U.S. This book also includes event studies of team ownership, assessment of human capital markets, analysis of the relationship between attendance and competitive balance, the components of fan demand in common the world over, and business decisions concerning attendance and pricing. There is already demand for comprehensive study of the sports business in the Pacific Rim as witnessed by this growth. This book will be of interest of researchers studying and/or teaching in the fields of sports economics and sports management as well as a general audience interested in business governance around the world.